(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
A well organised healthcare system is one of the pillars of a society’s social and economic infrastructure. Efficient healthcare system is one of the important indicators of development. In times of global epidemics Covid-19 healthcare seeking behaviour has become an important issue. People adjust their treatment modalities based on the health system. Poor families in particular have very limited access to medical care; they usually rely on government medical facilities because they cannot afford private treatment. On the other hand, even in rural areas, access to medical care limited due to lack of additional healthcare facilities. Therefore in rural area’s it is very important to diagnose the factors that influence the health seeking behaviour of the household. The Specific objectives of the study are to investigate health status of households across Purulia district using secondary data from NFHS- 4 (2015-2016) and to determine the factors that influencing health seeking behaviour of the sample households. We have visited randomly selected three villages of Kashipur block in Purulia district, West Bengal and surveyed two hundred households. To determine the factors that influencing household healthcare seeking behaviour we have fitted logit model. The explanatory variables monthly average family income, household head’s education, number of members in a household above 60 years, number of members in a household below 6 years, having at least one member who consume medicines during the whole year, effect of Covid-19 on income, effect of Covid-19 on health, social category, village residence have positive significant impact on the probability of household members seeking treatment from both government and private places. We consider ST as our base and find that the general community has significant impact on the household members receiving treatment from both government and private places. From the result we find that the major source of income of the sample households has no significant impact on the healthcare seeking behaviour of sample households.